2022
DOI: 10.3389/fmolb.2022.800638
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Angiotensinogen-Melatonin Ratio in Gestational Diabetes and Preeclampsia

Abstract: Background: A large research portfolio indicates that an activated renal renin-angiotensin system or a deficit on melatonin is associated with several cardiovascular pathologies. In this observational clinical study, we hypothesized that alterations in urinary melatonin or angiotensinogen levels may be altered in two common conditions, preeclampsia and gestational diabetes. Our study’s primary objective was to assess melatonin and angiotensinogen as novel disease biomarkers detectable and quantifiable in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…Our research has demonstrated that the deep breathing test's heart rate variability is a reliable method for examining cardiac dysautonomia in conditions related to cardiovascular and psychosocial health [77][78][79]. Angiotensinogen in first-morning urine is associated with a decreased nocturnal melatonin secretion [80] and has been increased in chronic kidney disease [81], preeclampsia, and gestational diabetes [69].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our research has demonstrated that the deep breathing test's heart rate variability is a reliable method for examining cardiac dysautonomia in conditions related to cardiovascular and psychosocial health [77][78][79]. Angiotensinogen in first-morning urine is associated with a decreased nocturnal melatonin secretion [80] and has been increased in chronic kidney disease [81], preeclampsia, and gestational diabetes [69].…”
Section: Discussionmentioning
confidence: 90%
“…Urinary 6-sulfatoxymelatonin (melatonin's metabolite) in the first-morning urine determines nighttime suppression of melatonin synthesis [65][66][67][68]. By measuring urinary 6-sulfatoximelatonin, we were able to identify preeclampsia, gestational diabetes [69], and social jetlag [70].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, subgroup analysis also suggested that the association between maternal GDM and childhood asthma was weakened after adjustment of the prevalence maternal gestational hypertensive disorders. These findings may suggest that maternal GDM and gestational hypertensive disorders may share some similar mechanisms which may also be related to the pathogenesis of asthma in offspring, such as inflammatory response of interleukin balance [ 31 ] and hormonal changes involving the renin-angiotensin system [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has been shown to regulate blood pressure and mitigate the development of hypertension in numerous animal models of renal programming ( 3 ). Recently, an increased urinary angiotensinogen/melatonin ratio was suggested to be an early biomarker for identification of gestational diabetes or pregnancy induced hypertension ( 136 ). In neonates, there is placental transfer of melatonin as endogenous melatonin production does not occur until 2–4 months of age and is known to be further delayed in preterm and FGR infants ( 134 ).…”
Section: Antioxidant Therapies Targeting Minimization Of Neonatal Kid...mentioning
confidence: 99%